A Descriptive Study Of Diet In Family Of Patients With Diabetes Mellitus Type 2 - Citra Windani Mambang Sari; Fitri Nurul Khotimah; Sri Pratiwi Hartati (Journal of Nursing Care, 2018)
Diet is one of the main factors related to various diseases including Diabetes Mellitus (DM). High carbohydrate, fat, protein, and low fiber diets can increase the risk of type 2 DM occurrence, especially in the patient’s family as a risk group. Previous research on students with DM families in Central Java still had a high-calorie food consumption pattern. The diversity of population, culture, and age may affect the results. Therefore, this study aimed to describe the diet in the family of patients with type 2 DM in the working area of Puskemas (Community Health Center) Garuda Bandung.This research used a quantitative descriptive method by purposive sampling technique. The respondents in this study involved 46 people who were the children of type 2 DM patients in the working area of Puskesmas Garuda. Dietary data obtained from the food record sheet for 3 days and was calculated using Nutrisurvey software in kilocalories (kcal) as the unit of measurement then the results were categorized based on Consensus Perkeni 2015. Data analysis was using frequency distribution.The results showed that 39 (84.8%) respondents in the diet category less than body requirements, 37 (80.4%) respondents in the category of sufficient carbohydrate intake, 39 (84.6%) respondents in the category of excess fat intake, 45 (97.8%) respondents in the category of adequate protein intake, and 41 (89.1%) respondents in the category of less fiber.The conclusions from this study that almost all families of patients with type 2 DM in the work area of Puskesmas Garuda were in the diet category less than body requirement but with the excess fat intake and less fiber. Based on these results, the nurses in Puskesmas are expected to optimize the outreach programs by addressing families of DM patients to make the diet as an attempt to prevent the risk in the family of patients with type 2 DM.Key words: Diet, DM patients’ families, food record. Gambaran Diet pada Keluarga Pasien Diabetes Melitus Tipe 2AbstrakDiet adalah salah satu faktor utama yang berhubungan dengan berbagai penyakit termasuk Diabetes Melitus (DM). Diet tinggi karbohidrat, lemak, protein, serta rendah serat dapat meningkatkan risiko kejadian DM tipe 2 terutama pada keluarga pasien sebagai kelompok berisiko. Penelitian sebelumnya pada mahasiswa dengan keluarga DM di Jawa Tengah masih memiliki pola konsumsi makanan yang tinggi kalori. Perbedaan populasi, budaya, serta usia mungkin akan mempengaruhi hasil. Oleh karena itu, tujuan penelitian ini untuk menggambarkan diet pada keluarga pasien DM tipe 2 di wilayah kerja Puskemas Garuda Kota Bandung.Penelitian ini menggunakan metode deskriptif kuantitatif dengan teknik purposive sampling. Responden dalam penelitian ini berjumlah 46 orang yang merupakan anak kandung pasien DM tipe 2 di Wilayah Kerja Puskesmas Garuda. Data diet diperoleh melalui lembar food record selama 3 hari dihitung mengunakan software Nutrisurvey dengan hasil ukur dalam kilokalori (kcal) yang kemudian hasilnya dikategorikan berdasarkan Konsensus Perkeni 2015. Analisis data menggunakan distribusi frekuensi.Hasil penelitian menujukkan bahwa sebanyak 39 (84,8%) responden dalam kategori diet kurang dari kebutuhan, sebanyak 37 (80,4%) responden dalam kategori asupan karbohidrat cukup, sebanyak 39 (84,6%) responden dalam kategori asupan lemak berlebih, sebanyak 45 (97,8%) responden dalam kategori asupan protein cukup, dan 41 (89,1%) responden dalam kategori serat kurang.Simpulan dari penelitian ini bahwa hampir seluruh keluarga pasien DM tipe 2 di wilayah kerja Puskesmas Garuda berada pada kategori diet kurang dari kebutuhan tetapi dengan asupan lemak berlebih dan serat yang kurang. Berdasarkan hasil tersebut, maka perawat puskesmas diharapkan dapat mengoptimalkan program luar gedung dengan menyasar keluarga penderita DM untuk menjadikan diet sebagai upaya untuk mencegah risiko DM pada keluarga pasien DM tipe 2.Kata kunci : Diet, food record, keluarga pasien DM.